Bagian Ilmu Kesehatan Gigi dan Mulut Fakultas Kedokteran Gigi Universitas Hasanuddin Makassar, Indonesia - Riskayanty Riskayanty; Nurul Fitriani R. D; Rasmidar Samad (Journal of Dentomaxillofacial Science, 2014)
Elderly people are particularly vulnerable to oral disease. Decreased function of the body can affect the aging process of the organic, and anorganic content in the elderly. The aim of this study was to determine the content of organic elements (total protein level), volume and pH of saliva in the elderly. This descriptive observational study with crosssectional design was performed in Tresna Werdha Gau Mabaji Social Institution, Gowa (n=30)with a simple random sampling technique using 30% of the total population and in Werdha Theodora Makassar nursing home with saturated sampling technique (n = 13). Anorganic contents were measured using spectophotometric and organic content of the total protein level of saliva was measured using an autoanalyzer tool kyltec in BPTP Laboratory Maros. Statistical analysis was performed with t-test using SPSS version 16. There were no significant differences between the anorganic (Ca2+,Mg2+, and phosphate) and organic elements content of saliva (total protein level), the volume of saliva and salivary pH in the elderly by sex and age groups. Yet, there are significant differences in the volume of saliva of elderly who consume drugs for systemic diseases. It is concluded that gender and age do not affect the anorganic (Ca,and phosphate)and organic element content of saliva (total protein content), the volume of saliva, and saliva pH in the elderly. Drugs consumed for systemic diseases does not affect the anorganic and organic element content of saliva and the pH of saliva in the elderly.